Salivary periostin levels as a non-invasive biomarker and their clinical correlates among healthy and periodontitis patients—a cross-sectional analytical study - Padalkar, Priyanka; Yadadi, Sunaina Shetty; Vivekanandan, Gopinath; Shetty, Shishir Ram; Andhare, Mangesh; Pashine, Aditi; Vinay, Vineet; Desai, Vijay; Shetty, Raghavendra M. (Frontiers in Dental Medicine, 2025)
BackgroundThe diagnosis of periodontitis is primarily through clinical and radiographic assessments. However, it is difficult for clinicians to detect incipient periodontitis during the routine clinical assessment. Identifying people at risk for periodontitis and tracking disease development need a dependable biomarker. Currently, no biomarkers meet all the criteria required for an ideal diagnostic test. Therefore, the clinical utility of salivary periostin as a potential screening tool for periodontitis warrants further investigation, particularly through large samples across diverse populations. The present study aimed to investigate salivary periostin levels as a biomarker in individuals with periodontitis and healthy controls.MethodsForty-five patients with generalized periodontitis stage III grade A/B and an equivalent number of periodontally healthy controls were evaluated for plaque index (PI), gingival index (GI), pocket probing depth (PPD), and clinical attachment level (CAL). Unstimulated salivary samples from all subjects were taken, and periostin levels were quantified using an ELISA kit.ResultsThe average salivary periostin levels were 4.63 in the healthy group and 1.24 in the periodontitis group (P < 0.05). The Spearman coefficient indicated a negative correlation between periostin levels and the gingival index (r = −0.761), plaque index (r = −0.780; P < 0.05), probing pocket depth (PPD) (r = −0.713; P < 0.05) and clinical attachment level (CAL) (r = −0.713; P < 0.05). Linear regression analysis validated the indirect correlation between salivary periostin levels and clinical indicators (Adjusted R square = 0.947).ConclusionsSalivary periostin levels are associated with periodontal disease. Salivary periostin levels indirectly influence as a non-invasive biomarker of periodontitis. The biomarker periostin is effective for evaluating both healthy and diseased periodontium.